(untitled) (Marketing Journal, 2025)
The article analyzes key challenges and prospects for developing innovation activities in higher education institutions, emphasizing the role of universities in scientific and technological progress. It examines international practices in digital transform ation, university -industry collaboration, and innovation infrastructure development. Strategic measures are proposed to strengthen the integration of universities into the innovation ecosystem.